Incidence and survival of patients with oligometastatic esophagogastric cancer: A multicenter cohort study. (August 2022) - Kroese, Tiuri E.; Christ, Sebastian M.; van Rossum, Peter S.N.; Burger, Matthijs D.L.; Buijs, George S.; Mühlematter, Urs; Andratschke, Nicolaus; Ruurda, Jelle P.; Hüllner, Martin; Gutschow, Christian A.; van Hillegersberg, Richard; Guckenberger, Matthias
Graphical abstract: Patients with metastatic esophagogastric cancer present in 25% with oligometastatic disease. Local treatment of OMD plus systemic therapy was associated with long-term overall survival. Highlights: Patients with metastatic esophagogastric cancer present in 25% with oligometastatic disease (OMD). Local treatment or systemic therapy for OMD improved overall survival (OS). OS after local plus systemic therapy was better compared with local or systemic therapy. Randomized controlled trials are warranted to confirm these results. Abstract: Purpose/Objective: This multicenter study assessed the incidence and survival of patients with esophagogastric cancer and oligometastatic disease (OMD) in two tertiary referral cancer centers in The Netherlands and Switzerland. Materials/Methods: Between 2010 and 2021, patients with metastatic esophagogastric cancer were identified. Patients with de-novo OMD were included (first-time diagnosis of ≤5 distant metastases on 18 F-FDG-PET/CT). Control of the primary tumor was considered in patients who underwent primary tumor resection or definitive chemoradiotherapy without locoregional recurrence. Treatment of OMD was categorized into (1) systemic therapy, (2) local treatment (stereotactic body radiotherapy or metastasectomy), (3) local plus systemic therapy, or (4) best supportive care. The primary outcomes were overall survival (OS) and independent prognostic factors for OS. Independent prognostic factors for OS were analyzed using multivariable Cox proportional hazard models. Results: In total, 830 patients with metastatic esophagogastric cancer were identified of whom 200 patients with de-novo OMD were included (24%). The majority of included patients had esophageal cancer (73%) with adenocarcinoma histology (79%) and metachronous OMD (52%). The primary tumor was controlled in 68%. Treatment of OMD was systemic therapy (25%), local treatment (43%), local plus systemic therapy (13%), or best supportive care (18%). Median follow-up was 14 months (interquartile range: 7–27). Median OS was 16 months (95% CI: 13–21). Improved OS was independently associated with local plus systemic therapy compared with systemic therapy alone (hazard ratio [HR] 0.47, 95% confidence interval [CI]: 0.25–0.87). Worse OS was independently associated with squamous cell carcinoma (HR 1.70, 95% CI: 1.07–2.74), bone oligometastases (HR 2.44, 95% CI: 1.28–4.68), brain oligometastases (HR 1.98, 95% CI: 1.05–4.69), and two metastatic locations (HR 2.07, 95% CI: 1.04–4.12). Median OS after local plus systemic therapy was 35 months (95% CI: 22-NA) as compared with 13 months (95% CI: 9–21, p < 0.001) after systemic therapy alone for OMD. Conclusion: Patients with metastatic esophagogastric cancer present in 25% with de-novo OMD. Local treatment of OMD plus systemic therapy was independently associated with long-term OS and independently improved OS when compared with systemic therapy alone. Randomized controlled trials are warranted to confirm these results.